PELATIHAN KEWIRAUSAHAAN MASYARAKAT BADUY DENGAN INOVASI UNTUK MENCAPAI SDGs - Abu Naim; Dadang Dadang; Sena Atmaja; Helmas Septiyo Hadi; Dindin Aminudin; Rina Ambarwati; Sugiyono Sugiyono; Andika Mugi Gumilang; Mardi Mardi (Jurnal Abdi Insani, 2026)
The global agenda for sustainable development requires the participation of the entire community, including local communities. The low entrepreneurial capacity of the community to build productive, innovative, and sustainable businesses is one of the main challenges faced by Indonesia. Micro-entrepreneurs are still very unfamiliar with business management, product innovation, marketing, and the Sustainable Development Goals (SDGs). Additionally, there is no international collaboration in community service programs, resulting in minimal exchange of knowledge and sustainable entrepreneurship practices. Through sustainable entrepreneurship training aligned with SDG values and international collaboration with MSU Malaysia, the aim of this activity is to enhance knowledge, skills, and motivation for entrepreneurship. Problem analysis, program design and architecture, field activity implementation, and evaluation and follow-up are the four stages that form the activity method. Between December 17 and 18, 2025, 200 people from the Baduy community attended the event in Ciboleger Village, Leuwidamar District, Lebak Regency, Banten Province. The results of the activity showed a significant increase in participants' understanding of entrepreneurship, product innovation, SDG concepts, and their desire to engage in business. Compared to the previous test, the average score of the participants increased significantly. They are also more open to business ideas that align with traditional values and environmental sustainability. A participatory approach can reduce challenges such as time constraints and variations in participants' education levels. Improving the entrepreneurial skills of the community has been shown to be a positive outcome of this initiative. This can also serve as a model for sustainable cooperation to support the achievement of SDGs at the local level. Keywords: Business_Innovation; International_Collaboration; Sustainable_Entrepreneurship; Community_Service; Sustainable_Development_Goals (SDGs)